THE USE OF FACEBOOK AND STUDENTS BEHAVIOR OF SMK PENERBANGAN PULAU BERAYAN DARAT IN MEDAN CITY - Krisna Gerda Simanjuntak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
The title of this research is “The Use of Facebook and Students Behavior of SMK Penerbangan Pulau Berayan Darat in Medan City. This study aims to determine the use of facebook and its effects on students behavior of SMK Penerbangan Pulau Berayan Darat Medan. This research used a qualitative descriptive methode that systematically illustrates, actual and accurate about the facts, characteristic and correlations between variables but it had no any hypothesis test. Theoretical approaches used in this research is the theory of uses and effects of media communication. In collecting the data made by interview, observation, library research and private document of informant facebook. The subject / informants in this research were 9 students of SMK Penerbangan Pulau Berayan Darat from class X and XI. In taking the sample done in sampling snowball method, meant to find one informant and further interview. The process go end when the researcher set the data has been bore, assumed it will find no newly things in interview. In collecting the data, done in May through June 2015, the location is SMK Penerbangan Pulau Berayan Darat, Jl. Bilal Ujung No 3/145 Medan, Telp 061-6621261. The result showed that students habit of SMK Penerbangan Pulau Berayan Darat Medan used facebook some while at home, some at school and some in intenet home. Some of them preferred to stay alone but some while gathering with friends. Some of them used facebook by laptop, some by hand phone while they were relax, still while learning in school-room. The result also showed were effects the use of facebook on students behavior of SMK Penerbangan Pulau Berayan Darat Medan. The positive effects were their behavior/personality become more open, more care others, more communicative, more socially flexible, more confident, then make them often discussion and worship. The negative effects were wasteful behavior, some time make quarrels, make them procrastinate other activities (such eating, sleeping late at night) and experiencing fraud. Other effect was to make them like to take photos. Whereas in the case of reading the information about fashion and see porno sites had no effect on behavior.